PARP‐1 modulates the expression of miR‐223 through histone acetylation to involve in the hydroquinone‐induced carcinogenesis of TK6 cells. Issue 9 (14th June 2022) - Ling, Xiaoxuan; Pan, Zhijie; Zhang, Haiqiao; Wu, Minhua; Gui, Zhiming; Yuan, Qian; Chen, Jialong; Peng, Jianming; Liu, Zhidong; Tan, Qiang; Huang, Dongsheng; Xiu, Liangchang; et al.
Abstract: The upstream regulators of microRNAs were rarely reported. Hydroquinone (HQ) is the main metabolite of benzene, one of the important environmental factors contributing to leukemia and lymphoma. In HQ‐induced malignant transformed TK6 (TK6‐HT) cells, the expression of PARP‐1 and miR‐223 were upregulated. When in PARP‐1 silencing TK6‐HT cells, miR‐223 was downregulated and the apoptotic cell number correspondingly increased. In TK6 cells treated with HQ for different terms, the expression of miR‐223 and PARP‐1 were dynamically observed and found to be decreased and increased, respectively. Trichostatin A could increase the expression of miR‐223, then the expression of HDAC1–2 and nuclear factor kappa B were found to be increased, but that of mH2A was decreased. PARP‐1 silencing inhibited the protein expression of H3Ac, mH2A, and H3K27ac. By co‐immunoprecipitation experiment, PARP‐1 and HDAC2 were found to form a regulatory complex. In conclusion, we demonstrated that the upregulation of PARP‐1 mediated activation of acetylation to promote the transcription of miR‐223 possibly via coregulating with HDAC2, an epigenetic regulation mechanism involved in cell malignant transformation resulting from long‐term exposure to HQ, in which course, H3K27ac might be a specific marker for the activation of histone H3, which also gives hints for benzene exposure research.